Chaplaincy in the Netherlands: The search for a professional and a religious identity (Tidsskrift for Praktisk Teologi, 2020)
This article presents an overview of the state of chaplaincy in the Netherlands. It sketches the history, religious and theological climate, training, organisation, and current practice. Two important recent developments are discussed: The rise of nondenominational spiritual care, and spiritual care - givers becoming involved in community care. Spiritual care in the Netherlands has gone through a long process of professionalisation, in which the relationship between the chaplain’s professionaland religious identities had to be continually redefined. It is argued that although Dutch spiritual care is still organised denominationally, spiritual caregivers share a common professional identity as professionals who focus on the search for meaning, belief systems, and ethics.